Allergic to the Twentieth Century: Intentional Communities and Therapeutic Landscapes in The Village and Safe. Issue 1 (2nd January 2017) - Bell, David
Abstract: The concept of therapeutic landscapes has been used to explore diverse spaces and places of healing or wellness, from hospitals to gardens, libraries to smoking areas. A central strand of this work considers rural and/or natural landscapes as affording particular healing experiences. In this paper, I draw on this lineage of work alongside research into the formation of intentional communities in rural settings and the body of writing on representations of rural landscapes and country life. The two representations I analyse are films: The Village (M. Night Shyamalan, 2004) and Safe (Todd Haynes, 1995). In the former, an apparent settler village in rural Pennsylvania is revealed, in the film's denouement, as an intentional community built as a retreat from the violence of contemporary urban life, guarded by Elders and a shared mythology about border-policing creatures. In Safe, the health hazards of modern suburban living, which lead the central character to develop multiple chemical sensitivity (MCS), can only be escaped by a similar retreat to a wilderness commune in the American desert. In both films, the spaces of rural life are constructed as therapeutic landscapes through their nostalgic, anti-modern withdrawal, and their protective boundary keeping.